2021
DOI: 10.1161/jaha.121.022222
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐Glucose Co‐Transporter Inhibitors and Atrial Fibrillation: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Background Sodium‐glucose co‐transporter (SGLT) inhibitors reduce cardiovascular outcomes including mortality in several populations; however, their effect on atrial fibrillation/flutter (AF) remains unclear. Our objective was to determine whether SGLT inhibitors reduce AF and whether a history of AF modifies the effect of SGLT inhibitors on the composite of heart failure hospitalization or cardiovascular death. Methods and Results We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 63 publications
0
42
0
2
Order By: Relevance
“…Several meta-analyses including all trials do show reductions in hemorrhagic stroke ( Tsai et al, 2021 ) and in total stroke ( Mascolo et al, 2021 ), which supports our results. Also, SGLT-2 inhibitors seem to reduce atrial fibrillation ( Pandey et al, 2021 ), which can also explain the stroke protection. It seems reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses including all trials do show reductions in hemorrhagic stroke ( Tsai et al, 2021 ) and in total stroke ( Mascolo et al, 2021 ), which supports our results. Also, SGLT-2 inhibitors seem to reduce atrial fibrillation ( Pandey et al, 2021 ), which can also explain the stroke protection. It seems reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies that address potential drug therapies that have the potential to reduce AF and HF risk in patients with elevated PAC and PVC counts would be of interest, for example sodium-glucose cotransporter-2 inhibitors as a preferred treatment for diabetic patients with PVCs. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis including all clinical trials that investigated SGLT2 inhibitors until December 2020 also reports a significant reduction of the incidence of atrial arrhythmias with an overall prevalence of approximately 1% of the study population [73]. A pooled analysis of 31 randomized clinical trials including more than 75,000 patients found that SGLT2 inhibitor use is associated with a lower incidence and recurrence of atrial fibrillation as well as with a reduced rate of cardiovascular outcomes [95]. Conversely, these findings could not be retraced in another meta-analysis dealing with a similar yet older database based on reported trial data until October 2019 [96].…”
Section: Sglt2 Inhibitors and Atrial Arrhythmias: Evidence From Clinical Trialsmentioning
confidence: 99%